Degradation of diphenhydramine by photo-Fenton using magnetically recoverable iron oxide nanoparticles as catalyst - Luisa M. Pastrana-Martínez (2015)
Iron oxide nanoparticles, with size ranging from 50 to 100 nm, were synthesized by a solvothermal method. The amounts of iron(III) chloride precursor (from 2.5 to 10.0 mmol) and sodium hydroxide (between 10 and 30 mmol) were varied along with the synthesis temperature (180 or 200 degrees C). Depending on the synthesis conditions, samples with magnetic properties consisting of magnetite (Fe3O4), or by a mixture of magnetite and maghemite (gamma-Fe2O3), and samples with no magnetism consisting of hematite (alpha-Fe2O3), were obtained. The catalytic activity of the materials was studied for the degradation of diphenhydramine using the photo-Fenton process. All materials performed well on the degradation of this emerging pollutant. The best compromise between catalytic activity and stability was obtained with pure magnetite nanoparticles prepared at 180 degrees C from a 4:1 molar ratio between sodium hydroxide and iron(III) chloride. This catalyst was used in further studies at different pH (2.8-11.0), catalyst loads (up to 200 mg L-1) and hydrogen peroxide concentrations (1-50 mM). Complete degradation of diphenhydramine with 78% of mineralization was achieved at relatively low leaching of iron species from the catalyst to the aqueous solution (1.9 mg L-1). Acidic pH (2.8) is preferable to neutral or alkaline pH (i.e. 6.0, 7.0 and 11.0) resulting from the higher efficiency of H2O2 to promote the formation of hydroxyl radicals under those conditions. Complete degradation of the pollutant can be obtained at acidic pH even at very low catalyst load (20 mg L-1). The use of stoichiometric H2O2 concentration allows for complete diphenhydramine conversion, maximum mineralization, and leaching of iron complying with European Directives. From recovery and reutilization experiments it was found that the selected magnetic catalyst might be easily recovered by magnetic separation, showing good stability and reusability properties.